Silicon Nanowire Field-Effect Transistor as Label-Free Detection of Hepatitis B Virus Proteins with Opposite Net Charges - Suh Kuan Yong (MDPI AG, 2021)
The prevalence of hepatitis B virus (HBV) is a global healthcare threat, particularly chronic hepatitis B (CHB) that might lead to hepatocellular carcinoma (HCC) should not be neglected. Although many types of HBV diagnosis detection methods are available, some technical challenges, such as the high cost or lack of practical feasibility, need to be overcome. In this study, the polycrystalline silicon nanowire field-effect transistors (pSiNWFETs) were fabricated through commercial process technology and then chemically functionalized for sensing hepatitis B virus surface antigen (HBsAg) and hepatitis B virus X protein (HBx) at the femto-molar level. These two proteins have been suggested to be related to the HCC development, while the former is also the hallmark for HBV diagnosis, and the latter is an RNA-binding protein. Interestingly, these two proteins carried opposite net charges, which could serve as complementary candidates for evaluating the charge-based sensing mechanism in the pSiNWFET. The measurements on the threshold voltage shifts of pSiNWFETs showed a consistent correspondence to the polarity of the charges on the proteins studied. We believe that this report can pave the way towards developing an approachable tool for biomedical applications.